Catalytic dehydration of glucose to 5‐hydroxymethylfurfural with a bifunctional metal‐organic framework. Issue 12 (24th June 2016) - Su, Ye; Chang, Ganggang; Zhang, Zhiguo; Xing, Huabin; Su, Baogen; Yang, Qiwei; Ren, Qilong; Yang, Yiwen; Bao, Zongbi
Abstract : Glucose conversion to 5‐hydroxymethylfurfural (HMF) generally undergoes catalytic isomerization reaction by Lewis acids followed by the catalytical dehydration to HMF with Brönsted acid. In this work, a sulfonic acid functionalized metal‐organic framework MIL‐101(Cr)‐SO3 H containing both Lewis acid and Brönsted acid sites, was examined as the catalyst for γ‐valerolactone‐mediated cascade reaction of glucose dehydration into HMF. Under the optimal reaction conditions, the batch heterogeneous reaction gave a HMF yield of 44.9% and selectivity of 45.8%. Reaction kinetics suggested that the glucose isomerization in GVL with 10 wt % water follows the second‐order kinetics with an apparent activation energy of 100.9 kJ mol −1 . Continuous reaction in the fixed‐bed reactor showed that the catalyst is highly stable and able to provide a steady HMF yield. This work presents a sustainable and green process for catalytic dehydration of biomass‐derived carbohydrate to HMF with a bifunctional metal‐organic framework. © 2016 American Institute of Chemical Engineers AIChE J, 62: 4403–4417, 2016